An Urban Memory Lost in Amnesia: Riverscape of Ankara - Yavuz, Irmak (ICONARCH International Congress of Architecture and Planning, 2017)
History often exhibits that the origins of human settlements are correlated with bodies of water. Rivers, in this respect, are denominated as forces that shape physical patterns as well as human activities in the design and planning literature. Operating as a source for different layers of activities, urban rivers have become a locus for memories to be formed. Yet, the path for urban rivers has transformed with the advent of the industrial age. The problems related to urban rivers are managed with singular remedies, causing the disappearance of riverscape together with its memory. Considering the age-old relationship between rivers and habitation, it is possible to argue that Ankara set a precedent in the sense that first; the city and its riverscape were in a subtle harmony regarding the economic, social and physical patterns of the city, resulting this collectivity to grew into a significant part of urban memory systems, and second; this urban memory was a subject to amnesia due to ruptures imposed on riverscape. The changing economic and spatial structure bringing along rapid and unplanned urbanization process, indirectly caused the disappearance of the riverscape of Ankara. It is expected that the paper will resolve the question that how riverscape with its multi-faceted dimensions is unfolded within the urban memory systems. Archive materials representing the spatial history of Ankara is investigated through the concepts of the study. With this, it aims to analyze the process as to how a riverscape, as part of an urban memory, might transform into an urban amnesia. In doing this, the paper explores the memory of Ankara’s riverscape in three stages. As an initial step the riverscape as an intrinsic value of the inhabitants in terms of economic and social activities are dwelled on. Subsequently, the making of riverscape is analyzed in light of the early plans and maps of Ankara considering the paradigms of the modern era. Finally, “how the riverscape of Ankara as an urban memory diminished" is examined through ruptures.